2009
DOI: 10.1108/09685220910993962
|View full text |Cite
|
Sign up to set email alerts
|

A canonical analysis of intentional information security breaches by insiders

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Of some significance, however, is the fact that phenomena which exist temporally prior to deterrence have rarely been addressed by IS security researchers. Indeed, only two papers by Straub (1990) and Shropshire (2009) have considered such phenomena by examining the issue of motive.…”
Section: Computer Abuse Timelinementioning
confidence: 99%
See 1 more Smart Citation
“…Of some significance, however, is the fact that phenomena which exist temporally prior to deterrence have rarely been addressed by IS security researchers. Indeed, only two papers by Straub (1990) and Shropshire (2009) have considered such phenomena by examining the issue of motive.…”
Section: Computer Abuse Timelinementioning
confidence: 99%
“…Such violations, although significant, are often dwarfed by a major insider abuse event in terms of their cost to the enterprise. Admittedly, there exists research which has focussed on the insider threat in terms of their motivation (Shropshire 2009;Straub 1990), deterrence (D'Arcy et al 2009;Harrington 1996;Hoffer and Straub 1989;Straub 1990;Straub et al 1992;Straub and Welke 1998), intention to offend (Foltz 2000;Lee and Lee 2002;Lee et al 2004;Workman and Gathegi 2007), and prevention (Willison 2002(Willison , 2006Willison and Backhouse 2006;Willison and Siponen 2009). However, this body of work is relatively modest when compared with the compliance literature, and warrants further consideration (Mahmood et al 2010;Warkentin and Willison 2009).…”
Section: Introduction: Is Security Threatsmentioning
confidence: 99%
“…Retaliatory behaviors may include but are not limited to calling in sick when not ill, gossiping about one's boss or coworkers, wasting company materials, damaging equipment or work processes. Shropshire (2009) recently conducted a canonical analysis of sixty-two intentional security breaches by insiders. His study indicated a positive correlation between four general variables and predictions of insider threat, each of which is observable by conscientious managers and/or supervisors.…”
Section: Relevant Researchmentioning
confidence: 99%
“…Typically, technical measures can assure to some extent the security against outside attacks by, e.g., general cryptographic protocols [1] and tailor-made protocols for particular application, e.g., for privacy in medicine [2], [3]. Operational security [4], [5] on the one hand and threats by insiders [6], [7] on the other hand remain the main source of concern.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on insider threats focused on identification [8]–[11], behavioral effects [6], [12], [13], particular areas of threat mitigation [14], or interfering with malicious behavior [15].…”
Section: Introductionmentioning
confidence: 99%